1964
DOI: 10.1152/jappl.1964.19.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical work in running

Abstract: The external and internal mechanical work in running has been measured through various procedures. Different from walking, in running the work due to the forward speed changes (variation of kinetic energy) and to the vertical displacement of the center of gravity (variation of potential energy), throughout the step cycle, are substantially in phase. The external work performed per kilometer is independent of speed, amounting to 0.25 kcal/kg km. The total mechanical work amounts to about 0.40–0.50 kcal/kg km. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
305
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(329 citation statements)
references
References 0 publications
15
305
0
4
Order By: Relevance
“…It has been shown that the physical musculoskeletal elastic components of the leg (tendons, ligaments, and muscles) are used to minimize metabolic cost while running (1,2,(8)(9)(10). However, no one, to date, has related the performance enhancements of running on surfaces of different stiffnesses to metabolic cost.…”
Section: In Their Groundbreaking Work Mcmahon and Greenementioning
confidence: 99%
“…It has been shown that the physical musculoskeletal elastic components of the leg (tendons, ligaments, and muscles) are used to minimize metabolic cost while running (1,2,(8)(9)(10). However, no one, to date, has related the performance enhancements of running on surfaces of different stiffnesses to metabolic cost.…”
Section: In Their Groundbreaking Work Mcmahon and Greenementioning
confidence: 99%
“…An almost sinusoidal pattern of the ground reaction force is observed in many types of fast animal and human locomotion (Cavagna et al, 1964(Cavagna et al, , 1977Alexander et al, 1986;Full et al, 1991;Farley et al, 1993). Although this includes both energy production (muscle fibers) and absorption (soft tissue, ligaments, muscles) the leg stiffness is surprisingly constant during the stance time.…”
Section: Introductionmentioning
confidence: 99%
“…During running, there is little energy saved by pendular-energy conservation because the gravitational potential energy and kinetic energy of the COM fluctuate in phase. Instead, the spring-like properties of muscles and tendons in the stance phase of running result in an exchange between the kinetic energy of the COM and the elastic energy stored in these tissues (Cavagna et al 1964(Cavagna et al , 1977Ker et al 1987;Roberts et al 1997). At fast speeds, when the inverted-pendulum mechanism of walking is impaired, this bouncing gait provides a highly effective means of reducing the metabolic cost of locomotion.…”
Section: Introductionmentioning
confidence: 99%